Religiöse Kleidung in der öffentlichen Schule in Deutschland und England: staatliche Neutralität und individuelle Rechte im Rechtsvergleich - Pottmeyer, Maria (Jus Ecclesiasticum, 2011)
How are Germany and England reacting to societys increasing religious heterogeneity? Using the handling of the dress code in state schools as an example, Maria Pottmeyer shows that England is deliberately making room for religious diversity whereas in Germany those in charge are trying to face it by prohibiting religious references at school. The author rejects this in her interpretation of the concept of neutrality for schools which is anchored in the Basic Law.